Overview of Anion Exchange Membranes Based on Ring Opening Metathesis Polymerization (ROMP). (2nd October 2021) - He, Zhenfeng; Wang, Guoqing; Wang, Chao; Guo, Li; Wei, Renbo; Song, Gang; Pan, Duo; Das, Rajib; Naik, Nithesh; Hu, Zhuolin; Guo, Zhanhu
Abstract: With very fast polymerization in mild reaction conditions and unique characteristic of double bonds in its synthesized polymer skeleton for further modification and functionalization, ring opening metathesis polymerization (ROMP) becomes one typical processing method to obtain anion exchange membrane (AEM) for fuel cells. In this paper, AEMs prepared by ROMP are reviewed. Polycyclooctene and polynorbornene AEMs with both good stability and high conductivity are achieved with different ion exchange groups such as quaternary ammonium, phosphorus and metal cations (such as bis(terpyridine)-ruthenium(II) and cobaltocenium). Polymer structure and ion channels are mainly constructed in the polymer skeleton to form the "ion channel" microphase-separated structure to improve its chemical stability and ionic conductivity. On the basis of selected ion exchange groups and optimized polymer skeleton, performances obtained in these ion exchange membranes (IEMs) and their corresponding fuel cell performances are summarized. These polycyclooctene and polynorbornene AEMs have excellent properties and promising performances in fuel cells. We believe that further exploration of this class of AEM may lead to practical applications.